Penaksiran Biomassa dan Karbon Tersimpan pada Ekosistem Hutan Mangrove di Kawasan Bandar Bakau Dumai - MANDARI, DESTI ZARLI; GUNAWAN, HARIS; ISDA, MAYTA NOVALIZA (Jurusan Biologi FMIPA Universitas Riau, 2016)
Mangrove forest ecosystem has a function as an absorber of Carbon dioxide (CO2) from the air and storecarbon in the form of biomass. The research was conducted in December 2014 until January 2015, andaimed to determine the total amount of above-ground biomass and the carbon stock as well as therelation of the three conditions of the development of mangrove forests in the area of Bandar Bakau,Dumai, Riau Province. The plot was made by using transect line plot method, 50 x 50 m in size with atotal of 3 plots along the coastline. Each plot contained 5 (five) sub-plots (10 x 10 m) that randomlydetermined. The results showed that along the transect line was found 10 species of mangrove, i.e.Xylocarpus granatum, Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorrhiza, Avicenniaalba, Avicennia marina, Sonneratia alba, Lumnitzera racemosa, Lumnitzera littorea, and Scyphiphorahydrophyllacea. The vegetation was dominated by Xylocarpus granatum with a density of 2128 trees/haand Rhizophora apiculata with a density of 1472 trees/ha. The highest total biomass and carbon stockgenerated by X. granatum with total biomass 78.6 ton/ha equivalent to 39.3 ton of C/ha. The total value ofbiomass produced from the whole plot is 115.85 ton/ha with a total carbon content stored at 57.91 tonC/ha.Key words: Above-ground Biomass, Carbon stored, Mangrove density, Xylocarpus granatum